2012
DOI: 10.1007/s13139-012-0141-0
|View full text |Cite
|
Sign up to set email alerts
|

Dual-time-point FDG PET/CT: Is It Useful for Lymph Node Staging in Patients with Non-Small-Cell Lung Cancer?

Abstract: Purpose Dual-time-point (DTP) FDG PET/CT has been shown to be useful for lymph node (LN) staging in patients with non-small-cell lung cancer (NSCLC). The aim of this study was to evaluate the LN staging ability of DTP FDG PET/CT in the predominant area of pulmonary tuberculosis. Methods Sixty-nine NSCLC patients underwent DTP PET/ CT. Regions of interest were placed on each LN of each station, and the maximum SUVs were measured. Three variables were obtained: (1) the SUV on the early scan (SUV early ), (2) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…Adenocarcinoma is known for low FDGavidity [29]. In this study, many adenocarcinoma cases were included, and adenocarcinoma showed a significantly lower SUVmax than squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Adenocarcinoma is known for low FDGavidity [29]. In this study, many adenocarcinoma cases were included, and adenocarcinoma showed a significantly lower SUVmax than squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…There are reports that F-18 FDG uptake by mediastinal lymph nodes was correlated with that by the primary nonsmall cell lung cancer [28,29]. Under the assumption that the ratio of two SUV values would be the significant variable, we evaluated the LN SUV/primary tumor SUV ratio.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, diffusion-weighted imaging of magnetic resonance imaging (MRI) might have a role in nodal staging of NSCLC [36]. In addition, dual time point PET/CT, obtaining delayed images might have a complementary role in nodal staging [25]. Although none of the studies included in this meta-analysis stated the use of time-of-flight (TOF) PET, TOF PET has known to provide a gain in image signal-to-noise ratio, lesion detectability, and accuracy of lesion uptake measurement [49].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the initial scan imaging is usually acquired after a minimum delay of 45 min for radiotracer distribution; however, there is no generally optimal delay time for either the initial time-point scan imaging or the time interval between the initial and delayed time points of image acquisition. In five of the included studies (10,(12)(13)(14)(15), imaging acquisition was performed 60 min and 120 min after the first injection. The other three studies (11,16,17) stated that delayed-scan imaging was obtained at 180 min, and one study (17) used 45 min as the initial scan time.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 654 patients were included in the analysis, with ages in the range of 35-89 years. One study (16) enrolled patients prospectively, four studies (11,(13)(14)(15) enrolled retrospectively, and the enrolling procedures of three studies (10,12,17) were unclear. Additionally, the patient selection in three studies (13,15,16) was performed in a consecutive manner, while the other five studies (10-12,14,17) did not report this information.…”
Section: Literature Search and Study Descriptionmentioning
confidence: 99%